The Association Between Ugandan Adolescents’ Viewing Of Specific Television Genres And Sexrelated Normative Beliefs And Behaviours - Miller, Ann Neville; Nalugya, Evangeline; Gabolya, Charles; Lagot, Sarah; Mulwanya, Richard; Kiva, Joseph; Nabaasaka, Grace; Chibita, Monica (Communicatio, 2016)
Growing evidence in Western nations indicates that exposure to high levels of sexual media content influences adolescents’ sexual attitudes and behaviours in those countries. Although media in many sub-Saharan markets contain increasingly higher levels of sexual content, little research has investigated the effects of that content on adolescents’ HIV-related risk and protective behaviours. This project used cultivation theory to examine Ugandan adolescents’ media use, and to test the relationship between their exposure to specific television genres and their sex-related normative beliefs and behaviours. Three hundred and sixty secondary school students from four purposively sampled schools filled out a questionnaire about their television viewing, their beliefs about the prevalence of sexual intercourse among their peers, and their own sexual behaviours. Preliminary evidence of relationships between watching comedy and cartoon programming, and high estimates of the proportion of adolescents who engage in sexual intercourse, were observed. Watching comedy programming and non- African programming was associated with the higher likelihood to have ever had sexual intercourse.
Keywords: adolescent sexual behaviours; media effects; sexual attitudes; sexual television content; television genres